THE EFFECT OF STUDENT ATTITUDE AND SOCIAL PRESENCE ON THE USE OF CHATGPT IN STUDENTS USING THE TECHNOLOGY ACCEPTANCE MODEL (TAM) - Radyta, Rissa Inkhah (EDUTECH, 2024)
This study aims to provide an analysis of the influence of student attitude on the perceived usefulness of ChatGPT, Influence of social presence on the social presence of ChatGPT, the influence of perceived usefulnes and perceived ease of use on the behavioral intention of ChatGPT on college student. this study was conducted on student of the Office Administration Education study program with a sample size of 156 from a population of 731 student determined using krejcie table with a significance level 0,05. The data analyzed technique that used in this study uses Stuctured Equation Modeling – Generalized Structured Component Analysis (SEM-GSCA) in processing using the GSCA pro application. The result of the research taken state that Student Attitude has a positive influence on Perceived Usefulness. Social presence has positive influence on Perceived Ease of Use. Perceived Usefulness and Perceived Ease of use has positive influence on Behavioral Intention. This research provides insight into ChatGPT technicians regarding system acceptance in influencing user intentions by providing a system that has Perceived Usefulness and Perceived ease of Use factors.